Preservation of ovarian endocrine function in patients with lymphoma: a systematic review - Hebatallah Ahmed Mohamed Moustafa; Al Shaimaa Ibrahim Rabie; Ahmed Abdullah Elberry; Ahmed Hassan Shaaban; Amany Mohamed Alboghdadly; Hind Khalid Goresh; Muath Fahmi Najjar; Mabrouk AL-Rasheedi; Raghda R. S. Hussein (Therapeutic Advances in Chronic Disease, 2025)
Background: Lymphomas represent various groups of cancers. Its treatment has a cytotoxic effect on all body tissues, especially female ovaries, yielding premature ovarian insufficiency. Objectives: This study aimed to compare the fertility and ovarian preserving role of gonadotropin-releasing hormone agonists (GnRH-a) when administered in conjunction with chemotherapy in women treated for lymphomas. Design: Only prospective clinical trials were included in this systematic review. Data sources and methods: We searched for pertinent studies in PubMed, Web of Science, Cochrane Library, Google Scholar, and Scopus till April 2025. Available prospective clinical trials comparing patients with Hodgkin lymphoma and non-Hodgkin lymphoma receiving concurrent chemotherapy and GnRH-a with patients receiving chemotherapy alone were included. The main outcomes were cyclic ovarian function (COF), pregnancy rate, follicle-stimulating hormone (FSH) level, luteinizing hormone level, estradiol level, and anti-Mullerian hormone (AMH) level. Cochrane’s risk of bias tool for clinical trials was used for the risk of bias assessment, and all the included studies were deemed of acceptable quality. Results: Twelve prospective clinical trials involving 733 women were analyzed, with 374 patients receiving GnRH-a and 359 as controls. The mean age of the GnRH-a group was 25.86 years, compared to 27.62 years in the control group. GnRH-a administration was associated with a notably higher COF, higher pregnancy rates, lower FSH levels, and higher AMH levels compared to controls. No significant difference between the groups was observed in estradiol levels. Conclusion: Co-administration of GnRH-a during chemotherapy in women with lymphoma appears to offer a protective effect against ovarian damage and supports fertility preservation in women with lymphoma. These findings advocate for the integration of GnRH-a into fertility preservation strategies, emphasizing its potential to improve long-term reproductive health in this vulnerable patient population. However, further high-quality, large-scale studies are warranted to standardize protocols and confirm these findings for broader clinical applications.